Practitioners' views on learning using children's peer interactions amongst under three year old children in Selangor, Malaysia / Farhana Wan Yunus. - Wan Yunus, Farhana (2019)
Research on children's peer interactions shows many benefits for children's development especially in developing children's social competence. Drawing on a case study data from a study that investigated peer interactions among under-three year old children in three Malaysian childcare centers, this paper provides a picture of how the children's peer interactions was understood by largely untrained practitioners at the start of the project, and how the complexity of children's lived experiences remained hidden to the practitioners until they took part in the video-stimulated recall (VSR) interviews based on children's peer interactions, and focus group discussions. The latter provided practitioners with an opportunity to deepen their thinking about children's peer interactions and to begin to see them as linked with learning. In particular, the practitioners perceived that (i) play; (ii) familiarity; and (iii) having friends constituted important learning for children during peer interactions at their early childcare centres. This has implications for understanding the roles of early childhood education practitioners to children's peer interactions as well as how practitioners can help support children's learning to make a social difference.